Braunwald's heart disease : A textbook of cardiovascular medicine Volume 2 - Zipes, Douglas P.; Libby, Peter; Bonow, Robert O. (Philadelphia Elsevier, 2019)
Contents: chronic Lung Disorders and Cardiovascular Disease; Transcatheter Treatment of Congenital Heart Disease; Approach to the Patient with Valvular Heart Disease; Obesity and Cardiometabolic Disease; Environmental Exposures and CVD; Approach to the Patient with Cardiac Arrhythmias; Cardio-oncology, Precision Medicine, and more. New information on clinical cardiovascular genetics; MR PET; MR device compatibility; fibrosis; fusion imaging; OCT; IVUS; left atrial appendage exclusion approaches and other topics.
Includes index
Keywords: Y đa khoa